[en] MANGUE FASHION: THE INFLUENCE OF THE MANGUEBEAT MOVEMENT ON THE FASHION SCENE OF THE STATE OF PERNAMBUCO - ALINE MOREIRA MONCORES (MAXWELL, 2007)
[pt] O trabalho faz parte de uma pesquisa descritiva, que visa analisar as contribuições da Cena Mangue à moda pernambucana. Observando as apropriações dos elementos simbólicos e iconográficos da Cena na produção intelectual e material de moda no Estado de Pernambuco. O estudo foi desenvolvido a partir da combinação de métodos de pesquisa, com consultas aos materiais disponíveis da época até os dias atuais (pesquisa bibliográfica e iconográfica) e uso de técnicas de entrevista. E finalmente visitas à cidade de Recife para coleta de documentos e entrevistas. === [en] That is descriptive research, which analyses the Cena Mangue´s contributions to the fashion of Pernambuco. By observing the appropriation of iconographic e symbolical elements of the Cena in both the intellectual and material productions, in the fashion of the state of Pernambuco. The study is composed through a combination of research methods, with consultation of materials available from that period until today (bibliographical and iconographic research), as well as through the use interview techniques. And finally, visits to the town Recife, in order to collect documents and interviews.